The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s40737-020-00211-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Quality of Life and Social Support Among Patients with Schizophrenia and Bipolar Disorder: A Cross-Sectional Study

Abstract: Many studies have demonstrated that quality of life (QoL) is poor among individuals suffering from severe mental illness like bipolar disorder (BD) and Schizophrenia due to various factors like residual symptoms, side effects of medication, and lack of social support. This study aims to explore the relationship between QoL and perceived social support among patients with schizophrenia and BD in remission and to identify the factors associated with QoL. A cross-sectional, descriptive study was carried out in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…In this context, people with schizophrenia may have difficulty in establishing social relationships and finding social support from the people around them. Studies have also found that individuals diagnosed with schizophrenia have low scores in the social dimension of quality of life (Dong et al, 2019; Munikanan et al, 2017; Prabhakaran et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, people with schizophrenia may have difficulty in establishing social relationships and finding social support from the people around them. Studies have also found that individuals diagnosed with schizophrenia have low scores in the social dimension of quality of life (Dong et al, 2019; Munikanan et al, 2017; Prabhakaran et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of other specific support categories in line with those identified from the perspective of family members could also be explored (Chronister et al, 2020). Moreover, it would be of interest to analyze the data by gender due to the importance of gender roles in social support, and include results more focused on positive points such as recovery (Corrigan & Phelan, 2004; Cullen et al, 2017) and quality of life (Prabhakaran et al, 2021). It would also be of interest to identify specific subgroups in which intervention in family and nonfamily networks could exert a stronger effect on clinical and functional evolution (Beckers et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, respondents indicated that they had higher friendships than other improvements, with someone even indicating that friendship was the most important gain. Previous studies have also shown that friendships made under community psychiatric rehabilitation centers are an important social support for patients, while social support is an important factor affecting the quality of life [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%